The Evolution of Orthodontic Treatment: From Braces to Aligners - Rami Osama Halawani, Ebrahim Younnis Almghrabi, Shadi Osama Halawani, Abdulwahed Abdullah Saleh Alzahrani, Saad Atiah Abdullah Alghamdi; Waad Mohammed Alasmari, Abdulrahman Saleh Alzahrani, SamahAwadOudah Alatawi, Amjad sultan albalawi, Yosef Abdullah Albalawi, Faisal Khalaf Alrashedi (Journal of International Crisis and Risk Communication Research, 2024)
This study explores the evolution of orthodontic treatment, tracing the transition from traditional braces to modern aligners. Utilizing secondary data sources, including historical records, clinical studies, and patient surveys, the research outlines the advancements in orthodontic technology and practices over the past century. Traditional metal braces, once the predominant method for correcting dental misalignments, offered reliable outcomes but often posed aesthetic and comfort challenges. The introduction of clear aligners marked a significant shift, addressing these concerns while maintaining effective treatment results. Key findings highlight that aligners, made from advanced materials, provide improved aesthetic appeal, enhanced comfort, and reduced treatment times compared to conventional methods. Furthermore, the study evaluates patient satisfaction and clinical outcomes, revealing a growing preference for aligners, particularly among adults. The synthesis of secondary data underscores the transformative impact of technological innovation on orthodontic practices, offering insights into future trends that may continue to redefine dental care. This evolution not only reflects advancements in materials science and digital technology but also a broader shift towards personalized and patient-centered healthcare solutions.